WHITESIDE TEST AND ENDOMETRIAL BIOPSY FOR DIAGNOSIS OF ENDOMETRITIS IN REPEAT BREEDING COWS - RAJA, S; DEVANATHAN, T G; KULASEKAR, K; PAZHANIVEL, N; BALACHANDRAN, C (The Indian Journal of Animal Reproduction, 2023)
Subclinical endometritis is considered to be one of the contributing factor for the repeat breeding problems in cows and hence diagnosis of subclinical endometritis becomes imperative. The present study was aimed to assess the efficacy of endometrial biopsy and white side test for diagnosis of subclinical endometritis. Twenty nine repeat breeding and ten cyclic cows with apparently normal fertility were utilized to compare the white side test, bacteriological culture using the cervical mucus and uterine biopsy. Twenty one cows were positive for white side test and twelve showed growth in bacteriological culture with different degrees of changes in the endomertium. It was concluded that histopathology of the endometrium may clearly indicate the future fertility status when compared to white side test and bacteriological culture analysis.